FISCAL EFFECTIVENESS UNDER REGIONAL ECONOMIC INTEGRATION: INDONESIAN AGRICULTURAL PERFORMANCE CASE - Nasrudin Nasrudin; Bonar M Sinaga; Muhammad Firdaus; Dedi Walujadi (Universitas Islam Indonesia, 2013)
AbstractThis paper investigates the effectiveness of fiscal policy in boosting agricultural sector performance and seeks the most effective policy in the presence of regional economic integration. It predicts the effectiveness of fiscal policy on the agricultural sector performance in four periods; the new order regime, the economic crisis, and pre and post China Free Trade Area (CAFTA). It also predicts the impact of fiscal policy on agricultural sector performance when CAFTA is fully implemented. It finds that fiscal policy is more effective in the optimum allocation of expenditures. It also finds that the agricultural sector can grow faster when the portion of capital expenditure increases.Keywords: Fiscal effectiveness, economic integration, agricultureJEL Classification Numbers: E62, F15, Q17AbstrakMakalah ini menyelidiki efektivitas kebijakan fiskal dalam mendorong kinerja sektor pertanian dan mencari kebijakan yang paling efektif dengan adanya integrasi ekonomi regional. Makalah ini memprediksi efektivitas kebijakan fiskal dalam meningkatkan kinerja sektor pertanian dalam empat periode; rezim orde baru, krisis ekonomi, sebelum pelaksanaan China Free Trade Area (CAFTA), dan setelah pelaksanaan CAFTA. Makalah ini juga memprediksi dampak kebijakan fiskal terhadap kinerja sektor pertanian saat CAFTA sepenuhnya dilaksanakan. Hasil analisis menemukan bahwa kebijakan fiskal lebih efektif dalam alokasi optimal dari pengeluaran. Analisis juga menemukan bahwa sektor pertanian dapat tumbuh lebih cepat ketika porsi peningkatan belanja modal meningkat.Keywords: Efektivitas fiskal, integrasi ekonomi, pertanianJEL Classification Numbers: E62, F15, Q17